Evaluation of Bridge Coffee Customer Expexrience - Hermawan, Devina; Iskandar, Budi Permadi (Journal of Business and Management, 2016)
Abstract. Along the years, we can not deny that coffee shop become a fast-growing business in Indonesia especially in urban city such as Jakarta, Bandung, Medan, Surabaya, and other cities. There is a really huge market this sector since drinking coffee is not longer a necessity but lifestyle. Bridge Coffee is on of those coffee players which produce premium roasted Indonesian coffee beans and other beverages for cafes, restaurant, corporation, and especially for end-customer. They are currently planning to open their first coffee shop in Bandung, which they named it Bridge Coffee Boutique and Dining. Coffee shop is a very competitive business, and attracting new customers is a consistent challenge. One of the best ways to attract new customers to Bridge Coffee Boutique and Dining is to offer something of value to change their